Analysis of Power Supply Mode and Circuit Topological Structure in Metro Vehicle Auxiliary Power System - CHENGYong-yi (机车电传动)
Structure and features about power supply network of metro vehicle auxiliary power source system including concreting power supply mode and grid connected power supply mode were introduced. The topological structure of auxiliary inverter circuit included two types, i.e. single inverter and double inverter, also the single inverter contained three types including two levels, three levels and highfrequency isolated types, and the double inverter contained two types including the circuit superimposition and the magnetic path superimposition. Analysis of the above mentioned two power supply modes were made for getting their advantages and disadvantages by comparison between them, and the opological structure characteristics of the different types of inverters were supplied, as well as the suggestion was brought up.